An individual-based model for collective cancer cell migration explains speed dynamics and phenotype variability in response to growth factors - Stichel, Damian; Middleton, Alistair; Müller, Benedikt; Depner, Sofia; Klingmüller, Ursula; Breuhahn, Kai; Matthäus, Franziska (npj Systems biology and applications, 2017)
In many cancers, spreading and the formation of metastasis involve the coordinated migration of many cells. An interdisciplinary team of researchers from Heidelberg and Frankfurt studied the collective movement of cultured lung cancer cells subject to chemical stimulation. Based on extensive data analysis a mathematical model was developed to explain the variety of migration behaviors observed under different treatments. The model describes the mechanics of compression, stretch, cell elasticity and force-regulated active motion—which in sum lead to coordination within large cell groups. Simulations demonstrate how these mechanical features affect cell coordination and collective behavior. In tests of potential medical treatment strategies, the model can be used to predict the effects of the drug on specific mechanical properties of single cells.